PRESCRIPTION COST ANALYSIS IN PATIENTS OF TYPE 2 DM AND HYPERTENSION JOINING CHRONIC DISEASE MANAGEMENT PROGRAM (PROLANIS) AT PUSKESMAS AFTER THE IMPLEMENTATION OF NATIONAL HEALTH INSURANCE - Arifin Santoso; Indriyati Hadi Sulistyaningrum; Hesti Dwi Widaryanti; Kusuma Arbianti; Chilmia Nurul Fatiha; Elmiawati Latifah (Universitas Muhammadiyah Magelang, 2023)
To improve the status of public health and carry out social security programs in the health sector, the government started to implement the National Health Insurance. This program covers the participants’ medical care expenses using the capitation system applied in health centers as the First-Level Health Facilities. BPJS Kesehatan has allocated some budget in the form of a capitation rate to first-level health facilities for hypertension and type 2 diabetes mellitus patients after the implementation of National Health Insurance. This research was carried out in 4 health centers, namely Lamper Tengah Health Center, Mangkang Health Center, Mijen Health Center, and Karanganyar Health Center. The data were collected retrospectively from the medical records of 800 patients. The data were analyzed descriptively to determine the prescription cost and Spearman's rho test was used to find the factors that influence the prescription cost. It was revealed that the average prescription cost for type 2 DM patients was IDR 142,293, and for hypertensive patients was IDR 112,735. The prescribing pattern in patients covered by Prolanis program for type 2 DM patients is a combination of glimepiride, metformin with a drug price of IDR 20,670. Factors that have an influence on prescription costs are diagnosis p= 0.033, type of drug (p= 0.000) and drug item (p= 0.000). This study concludes that the factors to influence the drug costs of Prolanis patients at the health centers of Semarang City were the patient's diagnosis, the type of drug given, and the number of drug items given.